ANTIMICROBIAL POTENTIAL OF BIOSYNTHESIZED SILVER NANOPARTICLE AGAINST HUMAN PATHOGEN PSEUDOMONAS AERUGINOSA AND KLEBSIELLA PNEUMONIAE - Dev, Anju; Kumar, Shyam; K J, Prashob Peter; Antony, Thomas (Innovare Journal of Life Sciences, 2018)
Â Objectives: The main objective of this investigation was to evaluate the potential of water extract from pteridophytes (Adiantum raddianum, Acrostichum aureum, and Christella dentata) in synthesizing silver nanoparticles (AgNPs) through eco-friendly routes and accessing their antibacterial activity. Methods: Water extract from pteridophytes (A. raddianum, A. aureum, and C. dentata) was used for synthesizing AgNPs. AgNPs formation was confirmed from the plasmonic absorbance spectra. Antimicrobial potential of synthesized particles was evaluated against human bacterial pathogens Staphylococcus aureus, Proteus species, Klebsiella pneumoniae, Pseudomonas aeruginosa, and Escherichia coli. The results were statistically validated using two-way ANOVA. Most active AgNPs were characterized using high-resolution transmission electron microscopy to access the morphology and size. Results: Water extract from the pteridophytes is capable of synthesizing AgNPs through green synthetic routes. AgNPs synthesized using water extract from A. raddianum showed a significant activity against P. aeruginosa followed by K. pneumoniae. These AgNPs possessed spherical morphology with size ranging between 10 and 20 nm. Conclusion: Novel bioactive formulations, particularly effective against P. aeruginosa and K. pneumoniae, can be developed through eco-friendly methods using water extract of A. raddianum